Karakteristik Kepemimpinan Rasulullah Dan Kepemimpinan Di Era Modern Dalam Bidang Pendidikan - Syahrul Fauzi; Nidaul Fajrin; Zainal Arifin (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This study aims to determine the analogy of leadership characteristics that have been applied by the Prophet with leadership in the modern era today. This study uses a qualitative approach with descriptive analysis methods, this type of research uses library research, while the data collection technique used is M3 (recording, analyzing, and critiquing) a finding. The results of this study show that there is an analogy between the leadership characteristics of the Apostles in the past and the leadership in the modern era at this time. First, the exemplary approach at the time of the Apostles with character-based leaders today where every leader must be able to become uswatun hasanah for each of his followers. Second, community-based leaders in the modern era who are able to provide motivation and build communication with an integrity approach at the time of the Prophet. Third, the democratic approach that existed in the leadership of the Prophet was intelligent in controlling emotions and dealing with problems. With this research, it is hoped that it can contribute to the science of education and hope that every leadership in educational institutions always imitates the characteristics possessed by the Prophet Shallallau 'alaihi wasallam.